Atmospheric Aerosols Detection Research with a Dual Field of View Lidar - Lv Lihui; Zhang Tianshu; Liu Cheng; Dong Yunsheng; Chen Zhenyi; Fan Guangqiang; Liu Yang; Liu Wenqing (Journal of Spectroscopy)
A dual field of view lidar system with two independent receivers is described to realize the detection of atmospheric aerosols. A CCD camera is attached to a backscatter lidar as a receiver to complement the data in the near-field range affected by the incomplete overlap between the laser beam and the receiver field of view. The signal detected by the CCD camera is corrected and finally glued with the signal of the backscatter lidar to retrieve the aerosol extinction coefficient with Fernald algorithm. The aerosol extinction profile and visibilities measured by the dual field of lidar had been compared with the results measured by another general backscatter lidar and a surface aerosol instrument, respectively. The results suggested that the dual field of view lidar based on a CCD camera is feasible and reliable. It could obtain the data both in the near and in the far range simultaneously, improving the detection accuracy of the lidar system effectively.